Executive Director’s Message - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2012)
There was, during the May 2012 Board of Directors meeting in Toronto, a great deal of discussion surrounding the work of the ORNAC Board as associated with the five pillars (National Conference Planning, Professional Practice, Advocacy, Research and Informatics, and Marketing). The appointed Chairs for each pillar have been planning and are beginning to work on initiatives that will support the implementation of the ORNAC Strategic Plan.